Emission Inventory for NH3, N2O, and CH4 of Animal Husbandry Activities: A case in Tho Vinh Commune, Kim Dong Distric, Hung Yen Province - Anh Le, Hoang; Hoa, Dang Thi Xuan; Cuong, Dinh Manh (VNU Journal of Science: Earth and Environmental Sciences, 2017)
Animal husbandry contributes to emission of greenhouse gases. The aim of this study is emission inventory of greenhouse gases (NH 3 , N 2 O and CH 4 ) from animal husbandry activities in Tho Vinh commune, Kim Dong district, Hung Yen province. Animal population in 2015 of the commune is 1.160 of pigs, 18 of buffalos, 62 of dairy cows, 22 of beefs, 18.360 of chickens, 3.913 of ducks, and 1.357 of musk ducks. Total estimated gas emissions from animal husbandy in Tho Vinh in 2015 were NH 3 (4.946 kg), N 2 O (812,65 kg), and CH 4 (12.084,16 kg) approximately. CH 4 emission from feed intake and cattle waste management processes from buffalo and cow were 6.568,82 kg and 5.515,34 kg, respectivly. NH 3 gas was mostly emitted by poultry (2.835,6 kg, accounted for 57%). N 2 O and CH 4 gases emitted mainly from pig were 417,6 kg (51%) and 4.640 kg (31%), respectively. The highest animal population and husbandry households concentrated in Dong Hung hamlet, which resulted in the highest gas emission. Keywords Emission inventory, Animals husbandry, Hung Yen References [1]. Bộ Tài nguyên và Môi trường, Báo cáo hiện trạng môi trường quốc gia giai đoạn 2011 - 2015, Bộ Tài nguyên và Môi trường, Hà Nội, 2015. [2]. Cục Chăn nuôi, Phát triển xản xuất chăn nuôi theo định hướng tái cơ cấu ngành nông nghiệp, 2017. [3]. Lã Văn Kính, Nguyễn Thanh Vân, Lê Phan Dũng, Đậu Văn Hải, Lê Đình Phùng, Jaap Schröder, Theun Vellinga, Kết quả điều tra quản lý chất thải chăn nuôi heo tại xã Gia Kiệm, Thống Nhất, Đồng Nai, Phân Viện Chăn nuôi Nam Bộ tại Đồng Nai, 2016. [4]. Vũ Thị Khánh Vân, Lê Đình Phùng, Vũ Dương Quỳnh, Nguyễn Kiêm Chiến, Vũ Chí Cương, Chu Mạnh Thắng, Nguyễn Hữu Cường, Hiện trạng quản lý chất thải và ô nhiễm môi trường chăn nuôi lợn trang trại ở Việt Nam, Nông nghiệp và phát triển nông thôn 1 (2013). [5]. UBND xã Thọ Vinh, Báo cáo tình hình phát triển kinh tế - xã hội 6 tháng đầu năm 2016 của xã Thọ Vinh huyện Kim Động, tỉnh Hưng Yên, UBND xã Thọ Vinh, Hưng Yên, 2016. [6]. K. Yamaji, T. Ohara, H. Akimoto, Regional-specific emission inventory for NH3, N2O, and CH4 via animal farming in South, Southeast, and East Asia, Atmospheric Environment 38 (2004) 7111. [7]. K. Yamaji, T. Ohara, H. Akimoto, A country-specific, high-resolution emission inventory for methane from livestock in Asia in 2000, Atmospheric Environment 37 (2003) 4393. [8]. J. Arogo, P. W. Westerman, A. J. Heber, A review of ammonia emissions from confined swine feeding operations, Transactions of the ASAE 46 (2003) 805. [9]. R. L. M. Schils, J. E. Olesen, A. Del Prado, J. F. Soussana, A review of farm level modelling approaches for mitigating greenhouse gas emissions from ruminant livestock systems, Livestock Science 112 (2007) 240. [10]. P. Crosson, L. Shalloo, D. O’Brien, G. J. Lanigan, P. A. Foley, T. M. Boland, D. A. Kenny, A review of whole farm systems models of greenhouse gas emissions from beef and dairy cattle production systems, Animal Feed Science and Technology 166 (2011) 29. [11]. H. Flessa, R. Ruser, P. Dörsch, T. Kamp, M. A. Jimenez, J. C. Munch, F. Beese, Integrated evaluation of greenhouse gas emissions (CO2, CH4, N2O) from two farming systems in southern Germany, Agriculture, Ecosystems & Environment 91 (2002) 175. [12]. M. J. Gibbs, D. E. Johnson. "Livestock Emissions." In: International Methane Emissions. US. Environmental Protection Agency, Climate Change Division, Washington, D.C., U.S.A.: 1993. [13]. IPCC. Guidelines for National Greenhouse Gas Inventories: Volume 4 - Agriculture, Forestry and Other Land Use Institute for Global Environmental Strategies (IGES), Japan: 2006. [14]. NRC. Nutrient Requirements of Dairy Cattle. National Academy Press, Washington, D.C. U.S.A.: 1989. [15]. NRC. Nutrient Requirements of Beef Cattle. National Academy Press, Washington, D.C. U.S.A: 1996. [16]. M. H. Jurgen. Animal Feeding and Nutrition (Sixth Edition). Kendall/Hunt Publishing Company, Dubuque, Iowa, U.S.A.: 1988.